Overcoming tet(X)-harboring tigecycline resistance: a study on the efficacy of tigecycline-apramycin combinations - Liu, Juan; Zheng, Si-Lin; Wu, Jing-Jing; Zheng, Mei; Cai, Da-Tong; Zhang, Yan; Sun, Jian; Liao, Xiao-Ping; Yu, Yang (Frontiers in Microbiology, 2024)
IntroductionThe emergence of the wide variety of novel tigecycline resistance tet(X) variants, including tet(X3), tet(X4), tet(X5), and tet(X6), has raised a serious threat to global public health and posed a significant challenge to the clinical treatment of multidrug-resistant bacterial infections.MethodsIn this study, we evaluated the synergism of tigecycline combining with other antibiotics as a means of overcoming the tet(X)-mediated resistance in Acinetobacter spp. Antibiotic synergistic efficacy was evaluated through in vitro chequerboard experiments, time-kill assays and dose–response curves. The in vivo synergistic effect of the combination was confirmed in a mouse model of thigh with neutrophilic granulocyte reduction. Additionally, combinations were tested for their ability to prevent high-level tigecycline-resistant mutants.ResultsWe found that the combinations of tigecycline with apramycin exhibited synergistic activity against tet(X)-harboring Acinetobacter spp. with FICI of 0.088. The MICTGC decreased more than 5 times in the presence of subinhibitory levels of apramycin. The combination showed in vitro synergism in time-kill assays and in vivo therapeutic effectiveness in the mouse thigh infection model.DiscussionThis study shed light on the synergism of tigecycline in combination with apramycin which offers a viable therapeutic alternative for infections caused by tet(X)-harboring Acinetobacter spp.